2020
DOI: 10.48550/arxiv.2008.04022
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quartic cumulant of baryon number in the presence of QCD critical point

D. Mroczek,
J. Noronha-Hostler,
A. R. Nava Acuna
et al.

Abstract: In the context of the ongoing search for the QCD critical point at the Relativistic Heavy-Ion Collider, we study the equation of state near the critical point in the temperature and baryon chemical potential plane. We use the parametric representation introduced in earlier literature, which maps the universal 3D Ising equation of state onto the QCD phase diagram using several non-universal parameters. We focus on the quartic cumulant of the baryon number, or baryon number susceptibility χ B 4 , which can be ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…Additionally, next generation experiments such as FAIR at the GSI ( √ s NN = 2.9 − 4.9 GeV) [5][6][7][8] and NICA in Dubna ( √ s NN = 3 − 5 GeV) [9,10] are being built to precisely determine the QCD equation of state (EOS) and the properties of the strongly interacting quark-gluon plasma (QGP) at large baryon densities. Relevant observables in this quest include fluctuations of conserved charges [11][12][13][14][15][16][17][18], flow [19], and particle yields [20]. For recent reviews see Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, next generation experiments such as FAIR at the GSI ( √ s NN = 2.9 − 4.9 GeV) [5][6][7][8] and NICA in Dubna ( √ s NN = 3 − 5 GeV) [9,10] are being built to precisely determine the QCD equation of state (EOS) and the properties of the strongly interacting quark-gluon plasma (QGP) at large baryon densities. Relevant observables in this quest include fluctuations of conserved charges [11][12][13][14][15][16][17][18], flow [19], and particle yields [20]. For recent reviews see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the most recent lattice QCD transition line obtained from the inflection point of the chiral condensate and its susceptibility in the crossover region, the values of κ 2 and κ 4 are 0.0153 (18) and 0.00032 (67), respectively [74]. It should be noted, however, that these expansion coefficients for the minimum of c 2 s and for the inflection of the chiral condensate do not need to agree, since the corresponding transition curves are actually different in the crossover region.…”
mentioning
confidence: 97%
“…[207]. Recently, the BEST EoS has been used to study the behavior of the critical fourthorder cumulant of baryon number on conjectured freezeout trajectories in the QCD phase diagram [208]. It was found that subleading and non-singular terms have a significant effect on the behavior of the fourth order cumulant (kurtosis).…”
Section: Eos With 3d-ising Model Critical Pointmentioning
confidence: 99%
“…[22]); this will likely change in the near future when better data from RHIC for the formation of QGP near a possible critical point will become available. The primary tool for this investigation will be critical fluctuations [23,24]. As scientists begin to look at the data from the high-statistics RHIC beam energy scan that has just concluded, they will analyze the data for the possible presence of such fluctuations because they can tell us something about the existence of a critical point in the QCD phase diagram.…”
Section: Diagnostics Focused On Quarksmentioning
confidence: 99%